NIHILISM DESTRUCTIVE EFFECTS IN LIFE REFLECTED IN ERNEST HEMINGWAY’S SHORT STORY ENTITLED A CLEAN, WELL-LIGHTED PLACE - Nisa, Kamilatun; Wulandari, Rini Susanti (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
This final project is about revealing the author‘s personal experience and world vision toward nihilism which are reflected in Hemingway‘s short story A Clean, Well-Lighted Place. The objectives of the study are; 1) to describe how nihilism is depicted in A Clean, Well-Lighted Place, 2) to describe how nihilism destructive effects are portrayed in A Clean, Well-Lighted Place, and 3) to reveal the author‘s experience and world vision toward nihilism in A Clean, Well-Lighted Place. The writer used qualitative analysis based on genetic structuralism approach by Lucien Goldman to analyze the author‘s personal experience of nihilism which reflected in A Clean, Well-Lighted Place. The data were gained by reading the novel, identifying, inventorying, selecting, reporting; and concluding. The results of this study are; First, nihilism is depicted in A Clean, Well-Lighted Place with believe in nothing, have no purpose of life, and have an impulse to destroy life. Second, the destructive effects of nihilism are portrayed with a tendency to put one’s life to an end and living a life in the depth despair. Third, A Clean, Well-Lighted Place is the reflection of the author‘s personal experiences and it also reveals the author‘s world vision toward nihilism that life is a war. The way people are eliminated from life is totally different from war. Some people are eliminated through sick or illness on his body while some other eliminated from inside. These people has meet death even before death taken his body. These people are thus who convicted nihilism that brings bad impacts.